Cutaneous Polyarteritis Nodosa Presenting Atypically with Severe Pharyngeal Ulceration - Bayanne Olabi; Justin C. Mason; Ziad Farah (Case Reports in Rheumatology)
Polyarteritis nodosa (PAN) is a multisystem, necrotising vasculitis of small- and medium-sized arteries with a predilection for the visceral vessels. Cutaneous PAN is a rare variant with symptomatic vasculitis limited to the skin, typically presenting as nodular lesions on the extremities with a propensity to ulcerate. We describe a rare case of histologically confirmed cutaneous PAN presenting in a 55-year-old Ghanaian woman with severe oropharyngeal ulceration. This was associated with dysphagia and significant weight loss. Oesophagoduodenoscopy showed that the ulceration extended throughout the oropharynx. Systemic polyarteritis nodosa was ruled out with magnetic resonance angiography. Our patient was treated successfully with corticosteroids and methotrexate. This case suggests that cutaneous PAN should be considered in the differential diagnosis of patients with oropharyngeal ulceration and that histological assessment is pivotal in establishing the diagnosis early in order to instigate appropriate therapy.